Bioreactor performance parameters for an industrially-promising methanotroph Methylomicrobium buryatense 5GB1. Issue 1 (December 2015) - Gilman, Alexey; Laurens, Lieve; Puri, Aaron; Chu, Frances; Pienkos, Philip; Lidstrom, Mary
Abstract Background Methane is a feedstock of interest for the future, both from natural gas and from renewable biogas sources. Methanotrophic bacteria have the potential to enable commercial methane bioconversion to value-added products such as fuels and chemicals. A strain of interest for such applications isMethylomicrobium buryatense 5GB1, due to its robust growth characteristics. However, to take advantage of the potential of this methanotroph, it is important to generate comprehensive bioreactor-based datasets for different growth conditions to compare bioprocess parameters. Results Datasets of growth parameters, gas utilization rates, and products (total biomass, extracted fatty acids, glycogen, excreted acids) were obtained for cultures ofM. buryatense 5GB1 grown in continuous culture under methane limitation and O2 limitation conditions. Additionally, experiments were performed involving unrestricted batch growth conditions with both methane and methanol as substrate. All four growth conditions show significant differences. The most notable changes are the high glycogen content and high formate excretion for cells grown on methanol (batch), and high O2 :CH4 utilization ratio for cells grown under methane limitation. Conclusions The results presented here represent the most comprehensive published bioreactor datasets for a gamma-proteobacterial methanotroph. This information shows that metabolism byM. buryatense 5GB1 differs significantly for each of the four conditions tested. O2 limitation resulted in the lowest relative O2 demand and fed-batch growth on methane the highest. Future studies are needed to understand the metabolic basis of these differences. However, these results suggest that both batch and continuous culture conditions have specific advantages, depending on the product of interest.